2020
DOI: 10.1002/jso.25901
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of texture analysis based on kinetic parametric maps from breast DCE‐MRI in classifying benign from malignant lesions

Abstract: Background and Objectives: To investigate the performance of texture analysis based on enhancement kinetic parametric maps derived from breast dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) in discriminating benign from malignant tumors.Methods: A total of 192 cases confirmed by histopathology were retrospectively selected from our Picture Archiving and Communication System, including 93 benign and 99 malignant tumors. Lesion areas were delineated semi-automatically, and six kinetic parametric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 64 publications
(80 reference statements)
2
7
0
Order By: Relevance
“…To determine Ki‐67 status, the features from the SI slope map were most frequently selected to construct the peritumoral RS, while the features from the E initial map were most frequently extracted to generate the intratumoral and combined RSs. These findings are partially consistent with those of a study conducted by Jiang et al, which also showed that functional parametric maps derived from breast DCE‐MRI included important information to discriminate between malignant and benign lesions 37 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To determine Ki‐67 status, the features from the SI slope map were most frequently selected to construct the peritumoral RS, while the features from the E initial map were most frequently extracted to generate the intratumoral and combined RSs. These findings are partially consistent with those of a study conducted by Jiang et al, which also showed that functional parametric maps derived from breast DCE‐MRI included important information to discriminate between malignant and benign lesions 37 …”
Section: Discussionsupporting
confidence: 92%
“…These findings are partially consistent with those of a study conducted by Jiang et al, which also showed that functional parametric maps derived from breast DCE-MRI included important information to discriminate between malignant and benign lesions. 37 For the features used in the RSs, most of the selected features were Gabor wavelet features, which can be used to comprehensively quantify tumor heterogeneity across different spatial scales at different directional orientations. 22,33 Two recent studies also showed that the Gabor wavelet features contain more detailed information about BC and were crucial components for construction of a radiomics model.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting the malignant signs with the highest risk to construct a nomogram can help distinguish benign and malignant lesions and improve the diagnostic value. Among them, the TIC curve, ADC value, mass edge, calcification morphology, age, and SWEmax were identified as independent predictors of benign and malignant tumors, which are the same as the previous study (9)(10)(11). No matter from the multivariable logistic regression analysis or the visualization of the nomogram, it can be seen that the edge spiculated of the tumor is the most powerful indicator to predict the malignant tumor.…”
Section: Discussionsupporting
confidence: 78%
“…In addition to morphological characteristics, hemodynamic characteristics also play an important role in predicting benign and malignant masses. Jiang (10) believes that the TIC curve can objectively and accurately assess the dynamic enhancement characteristics of the diseased tissue, and has high specificity and sensitivity for the differential diagnosis of breast diseases. The risk of malignancy of the washout TIC curve is 11.23 times that of the non-enhanced or continuously rising TIC curve.…”
Section: Discussionmentioning
confidence: 99%
“…With its rich artistic expression, it plays an important role in the field of painting and exists in oil painting in a unique form. Through the expression form of its own unique attributes, it shows the aesthetic feeling of vision and form in oil paintings [ 7 ]. The texture of different materials can show the characteristics of artistic language and image on the picture.…”
Section: Methods Of Oil Painting Style Formation and Schemamentioning
confidence: 99%